THE BEHAVIOUR OF RIVERBANK COMMUNITIES IN BARITO KUALA - Handy, Muhammad Rezky Noor; Kastina, Namira Regitha; Subiyakto, Bambang; Mutiani, Mutiani; Putra, Muhammad Adhitya Hidayat (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Rivers provide benefits to living creatures that live around riverbanks. However, river problems are a topic that is being widely discussed because they originate from the condition of the river or human behaviour. Bad human behaviour towards rivers will cause several problems. The behaviour of the riverbank community in Anjir Serapat Muara 1 Village, Barito Kuala Regency, still uses the river for daily activities, including bathing, washing, toilets, and public consumption. This activity can negatively impact the river's condition, especially pollution of river water quality due to people's behaviour and habits. Research objective: Describe the behaviour of riverbank communities in Anjir Serapat Muara Village 1. This research uses a qualitative approach with descriptive methods by describing the behaviour of riverbank communities in Anjir Serapat Muara Village 1 in Barito Kuala Regency. Observation, interviews, and documentation are used to carry out data collection techniques. Data analysis uses data reduction, data presentation, and conclusions. Test the validity of the data using extended observations, triangulation, and member checks. Research results: The behaviour of the riverbank community in Anjir Serapat Muara 1 Village still lacks cleanliness. It can be seen that the people there still throw rubbish in the river. This is because, in Anjir Serapat Muara 1 Village, there are no trash bins, people/vehicles carrying waste, public toilets, or clean water, which the community needs. The positive behaviour of the riverbank people of Anjir Serapat Muara 1 Village is that in fishing in the Barito River, they still maintain local wisdom by using traditional tools like rengge, rempa and unjun.